Seasonal Dynamics of Surface Soil Bulk Density in a Forested Catchment. Issue 4 (12th June 2015) - Nottingham, Adrienne C.; Thompson, James A.; Turk, Philip J.; Li, Qiuchen; Connolly, Stephanie J.
Abstract : Bulk density is a commonly measured property during field investigations of soils. Accurate and reliable bulk density measurements are critical for assessing soil quality as well as for converting mass‐based measurements to volume‐based values. Our objective was to determine if there are significant seasonal changes to the measured bulk density of surface soil horizons in a forested ecosystem. The frame method was used to measure bulk density at monthly intervals for 12 mo at 10 locations within a forested catchment. The measured bulk density was variable with time for all plots, with the strongest seasonality shown in Oi horizons. Seasonal trends in Oe and A horizons were less pronounced. Particularly for O horizons, it appears to be critical to consider the time of year when collecting bulk density data.